ASPECTS REGARDING PRODUCTION SCHEDULING BY USING ORDERING AND LOTTING MODELS - Grațian-Daniel GOLOȘIE (Fiabilitate şi Durabilitate, 2024)
This paper focuses on essential aspects of production scheduling in a specific job shop environment, with the primary objective of optimizing operational efficiency. Through a detailed simulation conducted in the Lekin application, a Job Shop Scheduling (JSS) system developed by M. Pinedo, we introduced four distinct jobs, each characterized by specific parameters, such as processing times at machines and due dates. We explore various scheduling rules, including Earliest Due-Date (EDD), Longest Processing Time (LPT), Shortest Processing Time (SPT), First Come First Serve (FCFS), Critical Ratio (CR), and Minimum Slack (MS), assessing their impact on system efficiency and performance. Each job, with its unique requirements and constraints, adds complexity to the production process, and our goal is to identify optimal strategies for managing these challenges in a dynamic and complex environment. The detailed analysis of simulation results and the comparison between different scheduling rules will contribute to the development of efficient methodologies for optimizing production scheduling in a diverse and constantly changing context. The outcomes of this paper have the potential to make significant contributions to enhancing the performance of production scheduling systems, addressing the specific requirements of contemporary industries.